An attempt to measure fluctuations of atmospheric pressure with laser interferometer. (December 2021) - Iizumi, Hideaki; Kajikawa, Hiroaki
Abstract: Fluctuations of atmospheric pressure caused by natural disasters have been observed in various parts of Japan. However, the evaluation method for the dynamic characteristics of the pressure gauges used for the observation has not been established. In this study, we aim to develop a measurement technique that can be used as a reference for evaluation of dynamic characteristics. We attempted to measure atmospheric pressure fluctuations with a laser displacement gauge based on the Michelson interferometry. The difference of optical path length between the two pressure cells of constant length was measured with the displacement gauge, and compared with the pressure change measured with a pressure gauge. The fluctuations of atmospheric pressure were measured by opening one pressure cell to the atmosphere. The measurement results of the displacement gauge showed the same trend as those of the pressure gauge.